Clinical and genetic diversities of Charcot‐Marie‐Tooth disease with MFN2 mutations in a large case study. Issue 3 (30th July 2017) - Ando, Masahiro; Hashiguchi, Akihiro; Okamoto, Yuji; Yoshimura, Akiko; Hiramatsu, Yu; Yuan, Junhui; Higuchi, Yujiro; Mitsui, Jun; Ishiura, Hiroyuki; Umemura, Ayako; Maruyama, Koichi; Matsushige, Takeshi; et al.
Abstract: Charcot‐Marie‐Tooth disease (CMT) constitutes a heterogeneous group affecting motor and sensory neurons in the peripheral nervous system. MFN2 mutations are the most common cause of axonal CMT. We describe the clinical and mutational spectra of CMT patients harboring MFN2 mutations in Japan. We analyzed 1, 334 unrelated patients with clinically suspected CMT referred by neurological and neuropediatric departments throughout Japan. We conducted mutation screening using a DNA microarray, targeted resequencing, and whole‐exome sequencing. We identified pathogenic or likely pathogenic MFN2 variants from 79 CMT patients, comprising 44 heterozygous and 1 compound heterozygous variants. A total of 15 novel variants were detected. An autosomal dominant family history was determined in 43 cases, and the remaining 36 cases were reported as sporadic with no family history. The mean onset age of CMT in these patients was 12 ± 14 (range 0–59) years. We observed neuropathic symptoms in all patients. Some had optic atrophy, vocal cord paralysis, or spasticity. We detected a compound heterozygous MFN2 mutation in a patient with a severe phenotype and the co‐occurrence of MFN2 and PMP22 mutations in a patient with an uncommon phenotype. MFN2 is the most frequent causative gene of CMT2 in Japan. We present 15 novel variants and broad clinical and mutational spectra of Japanese MFN2 ‐related CMT patients. Regardless of the onset age and inheritance pattern, MFN2 gene analysis should be performed. Combinations of causative genes should be considered to explain the phenotypic diversity.